Handgrip strength predicts physical and psychological domains of quality of life. - Tanaka, Gabriella Mayumi; Santos, Fernando Mateus; Neves, Lucas Melo; Gil, Saulo (Brazilian Journal of Global Health, 2023)
OBJETIVO: Este estudo investigou a associação entre força de preensão manual e qualidade de vida em diferentes domínios da qualidade de vida. MÉTODOS: Trata-se de um estudo transversal. Os participantes foram submetidos a uma entrevista semiestruturada para registro de idade, sexo, estado civil, etnia e renda familiar). Além disso, os indivíduos realizaram o teste de força de preensão manual. RESULTADOS: Foram avaliados duzentos indivíduos. No geral, a amostra foi composta por indivíduos de ambos os sexos (79% do sexo feminino) com idade entre 52±17 anos. O grupo de alta força apresentou valores elevados de qualidade de vida nos domínios físico (71,5 vs. 64,1 u.a.; IC95% 2,0 a 12,6; P=0,0066) e psicológico em comparação ao grupo de baixa força (72,0 vs. 67,4 u.a.; IC95% - 0,1 a 9,3; P=0,0214). Não foram observadas diferenças entre grupos para qualidade de vida nos domínios social e ambiental (ambos P>0,05). Foram encontradas associações positivas significantes entre força de preensão manual e qualidade de vida nos domínios físico e psicológico (R=0,27, P<0,0001 e R=0,17, P=0,0117, respectivamente). Não foi observada associação significativa entre força de preensão manual e qualidade de vida nos aspectos sociais e ambientais. O modelo de regressão linear ajustado mostrou associação positiva entre força de preensão manual e qualidade de vida física (β=0,74; IC95% 0,37 a 1,11; P<0,001) e psicológica (β=0,38; IC95% 0,06 a 0,71; P= 0,022) domínio. Em contrapartida, a força de preensão manual não se mostrou um preditor independente de qualidade de vida nos domínios social e ambiental (ambos P>0,05). CONCLUSÃO: Estes resultados revelam que a força de preensão manual é um preditor significativo e independente da qualidade de vida nos domínios físico e psicológico, mas não nos domínios social e ambiental. DESCRITORES: Qualidade de vida, Estado geral de saúde, Força. ABSTRACT OBJECTIVE: This study investigated the association between handgrip strength with quality of life in different domains of quality of life. METHODS: This is a cross-sectional study. Participants underwent a semi-structured interview to record age, sex, marital status, ethnicity, family income). Also, individuals performed the handgrip strength test. RESULTS: Two hundred individuals were evaluated. Overall, the sample comprised individuals of both sexes (79% female) aged 52±17 years. High strength group showed high values of quality of life in physical (71.5 vs. 64.1 a.u.; 95%CI 2.0 to 12.6; P=0.0066) and psychological domain in comparison with low strength group (72.0 vs. 67.4 a.u.; 95%CI -0.1 to 9.3; P=0.0214). No between-group differences were observed for quality of life in the social and environmental domains (both P>0.05). Significant positive associations were found between handgrip strength and quality of life in physical and psychological domain (R=0.27, P<0.0001 and R=0.17, P=0.0117, respectively). No significant association between handgrip strength and quality of life in social and environment was observed. Adjusted linear regression model showed a positive association between handgrip strength and quality of life in physical (β=0.74; 95%CI 0.37 to 1.11; P<0.001), and psychological (β=0.38; 95%CI 0.06 to 0.71; P=0.022) domain. In contrast, handgrip strength did not show to be an independent predictor of quality of life in social and environment domains (both P>0.05). CONCLUSION: These findings reveal handgrip strength is a significant and independent predictor of quality of life in physical and psychological domains, but not in social and environmental domains. DESCRIPTORS: Quality of life, General health status, Strength.